Home‐schooled children are thinner, leaner, and report better diets relative to traditionally schooled children. (20th September 2013) - Cardel, Michelle; Willig, Amanda L.; Dulin‐Keita, Akilah; Casazza, Krista; Cherrington, Andrea; Gunnarsdottir, Thrudur; Johnson, Susan L.; Peters, John C.; Hill, James O.; Allison, David B.; Fernández, José R.
<x xml:space="preserve">Abstract</x> Objective To examine and compare the relationships among diet, physical activity, and adiposity between home‐schooled children (HSC) and traditionally schooled children (TSC). Design and Methods Subjects were HSC (n = 47) and TSC (n = 48) aged 7‐12 years old. Dietary intakes were determined via two 24‐h recalls and physical activity was assessed with 7 days of accelerometry. Fat mass (FM), trunk fat, and percent body fat (%BF) were measured by dual‐energy X‐ray absorptiometry (DXA). Results Relative to HSC, TSC demonstrated significantly higher BMI percentiles, FM, trunk fat, and %BF; consumed 120 total kilocalories more per day; and reported increased intakes of trans fats, total sugar, added sugars, calcium, and lower intakes of fiber, fruits, and vegetables (P < 0.05). At lunch, TSC consumed significantly more calories, sugar, sodium, potassium, and calcium compared to HSC (P < 0.05). Physical activity did not differ between groups. Traditional schooling was associated with increased consumption of trans fat, sugar, calcium (P < 0.05); lower intakes of fiber, and fruits and vegetables (P < 0.05); and higher FM, %BF, and trunk fat (P < 0.01), after adjustment for covariates. Conclusions These data suggest HSC may consume diets that differ in energy and nutrient density relative to TSC, potentially contributing to differences in weight and adiposity.